Masculinity and veganism: the effect of linking vegan dishes with masculinity on men's attitudes toward vegan food - Scholz, Alma Elisabeth; Lenhart, Jan (Frontiers in Communication, 2023)
Introduction Vegetarian or vegan diets are not yet popular with most men, though they are beneficial for both health and the environment. Men's low preference for such diets might stem from the prevalent association of meat with masculinity, and of veganism with femininity. Accordingly, linking vegan nutrition to masculinity might help to develop a favorable attitude toward plant-based diets in men. The present study examined the effects of a masculine framing of vegan dishes on men's attitudes toward vegan food and veganism, and explored whether adherence to traditional forms of masculinity might increase the effects of masculine framing. Methods We conducted an online experiment with a 2 (man vs. woman) x 2 (conventional vs. masculine framing) design, in which 593 adults participated. We measured participants' attitudes toward vegan dishes (dish ratings, hunger ratings) and veganism (veganism ratings, vegan scenarios ratings), the perceived suitability of the dishes for men and women as well as men's identification with new forms of masculinity. Results We found that a masculine framing of vegan dishes influenced the gender association of the dishes, weakening the link to femininity. However, masculine framing did not influence men's or women's attitudes toward the presented vegan dishes or veganism in general. Although the extent to which men identified with new forms of masculinity correlated positively with favorable attitudes toward veganism, new masculinity identification did - with an exception for the rating of the presented dishes - not moderate the effect of the experimental condition. Discussion Our findings suggest that the potency of a short-term intervention might not be sufficient to counterbalance the prevailing feminine connotations associated with veganism. Thus, we encourage further exploration of masculine framing to improve men's perception of vegan food and the vegan concept, but with stronger stimuli and/or longer intervention duration.